Educational Policies Committee, Minutes, February 2019 - (:unkn) unknown (Valdosta State University Archives and Special Collections, 2019)
Educational Policies Committee Minutes from February 13, 2019 Meeting In attendance: Robert Smith; Sharon Gravett; Kelly Davidson; Nicole Alemanne; Stanley Jones; Laura Carter; Ryan Hogan; Lisa Long; Christy Croft; Ken Smith; Samantha Paul; Kendrick Coleman; Greg Henderson; Krupesh Patel; Matthew Kolakowski; Educational Policies Committee Meeting February 26, 2019 In attendance: Robert Smith; Sharon Gravett; Ryan Hogan; Kelly Davidson; Jie Fowler; Lisa Long; Christy Croft; Chunlei Liu; Ken Smith; Samantha Paul; Krupesh Patel; Matthew Kolokowski;
2 electronic documents (PDF).
Keywords: Faculty Senate (Valdosta State University); Minutes (Records)